Characterization of Lagrangian Submanifolds by Geometric Inequalities in Complex Space Forms - Lamia Saeed Alqahtani (Advances in Mathematical Physics, 2021)
In this paper, we give an estimate of the first eigenvalue of the Laplace operator on a Lagrangian submanifold Mn minimally immersed in a complex space form. We provide sufficient conditions for a Lagrangian minimal submanifold in a complex space form with Ricci curvature bound to be isometric to a standard sphere Sn. We also obtain Simons-type inequality for same ambient space form.